Hospitalidad y fidelización del cliente en el alojamiento Boulevard 251 Riverside Apartments, 2022 - Gratelly Aguilar, Lilian del Rosario (2023)
The objective of the research was to determine the relationship between hospitality and customer loyalty in the Boulevard 251 Riverside Apartments, 2022 accommodation, an applied type of study was chosen, descriptive - correlational level and non-experimental design, included 309 customers as a population; For the collection of information, the survey was used as a technique and the questionnaire as instruments. After verifying the results, it was established that hospitality has been developing on a regular basis (26%), this is due to the fact that the staff sometimes warmly welcomes customers upon their arrival at the establishment, as well as The accommodation rarely offered you any type of gift or token of appreciation for your stay, likewise, customer loyalty is rated as average (28%) since they almost always ask questions about their needs and desires, and sometimes innovate in their services it offers, as well as sometimes using social networks for better communication with the client. Finally, there is a significant relationship at the 0.000 level between hospitality and customer loyalty with a coefficient of 0.793 being considerable positive.